The effect of motivation of success of university students on personal-professional competence: Mediation role of lifelong learning tendency - Halil Ekşi; Mustafa Özgenel; Esin Metlilo (International Journal of Evaluation and Research in Education (IJERE), 2020)
In this study, the relationship between motivations for success, personal-professional competencies and lifelong learning tendencies of university students were investigated. The study group consists of 344 University students from Turkey and Kosovo. In this research, the collection of data was done by “Personal-Professional Competencies Perception Scale, “Success Oriented Motivation Scale” and “Lifelong Learning Tendency Scale”. In order to determine the relationship between variables in the analysis of the data, correlation analysis was performed and tested with the structural equation model. According to the results of the research; there was a positive significant correlation between motivation for success and personal professional competence, and a positive significant relationship between lifelong learning and personal-professional competence. Motivation for success positively affects personal-professional competencies and lifelong learning tendencies. It has been determined that lifelong learning tendency is a partial tool in this relationship.